Analisis Yuridis Pertanggungjawaban Hukum Pidana Korporasi Menurut Teori Kepastian Hukum Jan Michiel Otto - Suhartoyo, Suhartoyo (International Journal Labs, 2025)
This paper discusses corporate criminal liability in Indonesia using Jan Michiel Otto's theory of legal certainty. This study aims to identify the corporate criminal liability system, analyze the enforcement of corporate criminal law, and develop corporate criminal law in Indonesia. The results of the study indicate that corporations can be held accountable for criminal acts committed by individuals or groups within the scope of the corporation. Effective law enforcement requires law enforcement agencies that have the authority to ensure legal certainty. Strict criminal sanctions and fines can provide a deterrent effect for perpetrators of corporate crimes and prevent similar crimes from occurring in the future.